Karakteristik Sensoris Chikuwa dengan Perbedaan Bahan Baku Surimi Ikan - Dwi Inda Sari; Herpandi Herpandi; Reistha Warayu; Siti Hanggita Rachmawati (Universitas Sriwijaya, 2021)
Increased production of aquacultured freshwater fish, such as Pangasius pangasius, Oreochromis niloticus, and Clarias batrachus, wich have low commercial value as potential alternative raw materials for surimi. This study aimed to determine the sensory characteristics of chikuwa produced using different raw materials of surimi and increase the diversity of processed fishery products that are highly nutritious with recommended physical quality. This research used the randomized block design (RBD) method with three repetitions. The treatment used were the difference in raw materials of surimi, P1 (Pangasius pangasius), P2 (Oreochromis niloticus) and P3 (Clarias batrachus). Parameters in this research included physical analysis of surimi (gel strength), chemical analysis of surimi (protein content and moisture content), and chikuwa sensory analysis. The results showed that Pangasius pangasius had a significant effect on surimi gel strength, surimi protein content and surimi water content, but had no significant effect on Oreochromis niloticus and Clarias batrachus. Based on the chemical analysis results, all raw materials for surimi have met the standard of SNI 01-2694-2013 except for Pangasius pangasius surimi protein (11,94%). Different raw materials of surimi had a significant effect on the appearance, taste, color, and texture of the organoleptic test. However, it had no significant effect on the chikuwa aroma parameters. Chikuwa (P1) produced the best characteristics from an organoleptic.